PENGEMBANGAN VIDEO PEMBELAJARAN ANIMATION TIPS AND TRICK MATERI KPK DAN FPB KELAS IV SD MUHAMMADIYAH 2 PONTIANAK - Lika Ardiani (Universitas Tanjungpura, 2022)
This study is aiming to describe the form, validity level, analyze the level of completion of students’ scores and analyze the responses of teachers and students on the product results of the development of animation tips and trick learning video for the fourth grade on FPB and KPK in SD Muhammadiyah 2 Pontianak. This research used research and development (RnD) method adapted by Thiagarajan 4D design development model. The data sources of this study are the results of validation of three validators, the results of small-scale trials of students, and also teacher’sand students’ responses related to the products that have been displayed. This research data collection techniques are validator validation questionnaire, questions test for students, response questionnaires and documentation during the use of learning videos by students. The resultsshowed during the development process of video learning animation tips and trick, they went through 3 stages, namely define, design, and development, while the dessimination stage can't be implemented yet. The average level of validity of learning videos from the design aspect of 4,75 ofcriteria is very valid and from the learning aspect of 4,9 critical is very valid. Small-scale completion rates earned an average percentage of 77% of good-earned people. The learning video received a very good response from teachers and students.